Apoptosis Transcriptional Profile Induced by Porphyromonas gingivalis HmuY. (18th March 2019) - Carvalho-Filho, Paulo C.; Moura-Costa, Lilia F.; Pimentel, Ana C. M.; Lopes, Mabel P. P.; Freitas, Sibelle A.; Miranda, Patrícia M.; Costa, Ryan S.; Figueirêdo, Camila A. V.; Meyer, Roberto; Gomes-Filho, Isaac S.; Olczak, Teresa; Xavier, Márcia T.; et al.
Abstract : This study aimed at evaluating the transcriptional profile of apoptosis-related genes after in vitro stimulation of peripheral blood mononuclear cells (PBMCs) derived from individuals with periodontitis (P) and healthy nonperiodontitis (NP) control subjects with P. gingivalis HmuY protein. PBMCs from the P and NP groups were stimulated with HmuY P. gingivalis protein, and the expression of genes related to apoptosis was assessed by custom real-time polymerase chain reaction array (Custom RT 2 PCR Array). Compared with the NP group, the P group showed low relative levels of apoptosis-related gene expression, downregulated for FAS, FAS ligand, TNFSF10 (TRAIL), BAK1, CASP9, and APAF1 after P. gingivalis HmuY protein stimulation. Furthermore, the P group exhibited low levels of relative gene expression, downregulated for CASP7 when the cells were not stimulated. Our data suggest that P. gingivalis HmuY protein might participate differently in the modulation of the intrinsic and extrinsic apoptosis pathways.